PENGARUH MEDIA PEMBELAJARAN FISIKA BERBASIS MULTIMEDIA INTERAKTIF MENGGUNAKAN SOFTWARE ADOBE FLASH CS3 PROFESSIONAL TERHADAP HASIL BELAJAR SISWA KELAS X DI SMA PGRI PANGKALAN KERSIK TUNGKAL JAYA - Susanto, Rudy; Zulkarnain, Agus; Lubis, Patricia (PROSIDING SEMINAR NASIONAL PROGRAM PASCASARJANA UNIVERSITAS PGRI PALEMBANG, 2018)
This study aims to know the influence of interactive physics-based multimedia learning media using Adobe Flash CS3 Professional software on the results of students' study of class X in SMA PGRI Pangkalan Kersik Tungkal Jaya. Variable of research is dependent variable that is result of student learning and independent variable that is learning media physics based on interactive multimedia using Adobe Flash CS3 Professional software. The population in this study is all students of class X MIA in SMA PGRI Pangkalan Kersik Tungkal Jaya which amounted to 104 students. The sample in this study was taken by random sampling technique with the number of samples of 70 students divided into two classes namely class X MIA 2 as an experimental class who received learning treatment using interactive multimedia with the number of 35 students and students of class X MIA 1 as a control class treated conventional approach with 35 students. Techniques of collecting data using tests and documentation. The analytical technique used in this study is the right-t test. The result of calculation of data analysis obtained the average value of experimental class 77,56 and the average value of control class 67,90, with significant level of α = 0,05 got ttable that is 1,697 and tcal is 4.59. Based on the results of data calculations, it can be concluded that there is the influence of interactive physics-based multimedia learning media using Adobe Flash CS3 Professional software on the results of students' study of class X in SMA PGRI Pangkalan Kersik Tungkal Jaya..